2014
DOI: 10.1002/embj.201387205
|View full text |Cite
|
Sign up to set email alerts
|

Human telomerase specialization for repeat synthesis by unique handling of primer-template duplex

Abstract: With eukaryotic genome replication, incomplete telomere synthesis results in chromosome shortening and eventual compromise of genome stability. Telomerase counteracts this terminal sequence loss by synthesizing telomeric repeats through repeated cycles of reverse transcription of its internal RNA template. Using human telomerase domain-complementation assays for telomerase reverse transcriptase protein (TERT) and RNA in combination with the first direct footprinting assay for telomerase association with bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(101 citation statements)
references
References 63 publications
9
92
0
Order By: Relevance
“…It is possible that the substantial steady-state pool of hTERT-free hTR RNP (43) is not competent for active RNP assembly. This suggestion is consistent with poor assembly of active RNP by mixing hTERT and hTR cell extracts or separately folded subunits in vitro (58). It will be interesting to apply the in vivo cross-linking approach in combination with competition assays to examine the cell cycle dynamics of telomerase holoenzyme subunit interactions in budding yeast, which is suggested to include disassembly of the catalytic core (52).…”
Section: Discussionmentioning
confidence: 56%
“…It is possible that the substantial steady-state pool of hTERT-free hTR RNP (43) is not competent for active RNP assembly. This suggestion is consistent with poor assembly of active RNP by mixing hTERT and hTR cell extracts or separately folded subunits in vitro (58). It will be interesting to apply the in vivo cross-linking approach in combination with competition assays to examine the cell cycle dynamics of telomerase holoenzyme subunit interactions in budding yeast, which is suggested to include disassembly of the catalytic core (52).…”
Section: Discussionmentioning
confidence: 56%
“…The arms are entirely dispensable for in vitro activity, since a further-miniaturized allele consisting only of the 170-nt core is also able to reconstitute activity to Mini-T levels (Qiao and Cech 2008), indicating that the core is the only portion required for basal activity. For the human enzyme, in vitro activity can be reconstituted by similarly combining TERT with RNA core nucleotides 33-191, although human telomerase also requires an 87-nt element outside its core, CR4/5, either provided in trans or tethered to the core (Autexier et al 1996;Mitchell and Collins 2000;Wu and Collins 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have demonstrated that within the telomerase catalytic core, both TERT and TER interact with ssDNA. The TERT N-terminal (TEN) domain stimulates active-site use of a short primertemplate hybrid, while the remainder of TERT provides some functional recognition and physical protection of ssDNA (31). Within TER, the template binds to the ssDNA 3= end by hybridization, and other RNA motifs contribute to template placement in the active site (9,31).…”
mentioning
confidence: 99%
“…The TERT N-terminal (TEN) domain stimulates active-site use of a short primertemplate hybrid, while the remainder of TERT provides some functional recognition and physical protection of ssDNA (31). Within TER, the template binds to the ssDNA 3= end by hybridization, and other RNA motifs contribute to template placement in the active site (9,31). Additional telomerase holoenzyme proteins augment the activity of the catalytic core in vitro, but the relation of these in vitro activities to their roles in vivo remains unclear.…”
mentioning
confidence: 99%